Elucidating Afrocentricity as a contemporary theoretical stance through ’epistemic disobedience’ - Mugambiwa, Shingirai Stanley (Technium Social Sciences Journal, 2021)
The use of Afrocentricity as a contemporary theoretical lens has triggered remarkable debate among African scholars. There is growing contestation among African intellectuals on the future of knowledge construction in the wake of the collapse of colonization in Africa. The contestation on the applicability of the Afrocentricity as a theory is largely triggered by the assumed superiority of Western thought. One of the major proponents of Afrocentricity Melefe Kete Asante has prompted an interesting question ‘Why have Africans been shut out of global development?’ The question attracts the need for African scholarship to take into consideration a context based theoretical standpoint and methodology. Nevertheless, the quest for a purely African based thought is clashed by postmodernists who contend that there is no such thing as “Africans” because there are many different types of Africans and all Africans are not equal. It is from this standpoint that this paper seeks to position Afrocentricity as a fundamental theoretical perspective in African scholarship. Afrocentricity is considered to be a catalyst of change whose goal is to restore the African understanding of the world. As such, through what some scholars have termed “epistemic disobedience” which is a form of epistemic revolt in favour of decolonisation of thought, this paper provides a critical analysis of the relevance of Afrocentricity as a theoretical standpoint.